Reduced mucosal immunity to poliovirus after cessation of trivalent oral polio vaccine. Issue 8 (3rd August 2021) - Zhao, Ting; Li, Jing; Shi, Hongyuan; Ye, Hui; Ma, Rufei; Fu, Yuting; Liu, Xiaochang; Li, Guoliang; Yang, Xiaolei; Zhao, Zhimei; Yang, Jingsi
ABSTRACT: The switch from using only trivalent oral polio vaccine (tOPV) to sequential schedules combining inactivated poliovirus vaccine (IPV) and bivalent oral polio vaccine (bOPV) for polio vaccination will cause changes to mucosal immunity against polio in infants, which plays an important role in preventing the poliovirus spread. Here, we analyzed mucosal immunity against poliovirus in the intestine during different sequential vaccination schedules. We conducted clinical trials in Guangxi Province, China on 1, 200 2-month-old infants who were randomly assigned to one of three vaccination schedule groups: IPV-bOPV-bOPV, IPV-IPV-tOPV, and IPV-IPV-bOPV, with vaccine doses administered at 8, 12, and 16 weeks of age. Stool samples were collected from 10% of participants in each group before administration of the second vaccine doses and at 1, 2, and 4 weeks after the administrations of the second and third vaccine doses. Immunoglobulin A (IgA) in the stool samples was measured to analyze the mucosal immune response in the intestine. Because of the absence of poliovirus type 2 in bOPV, the vaccination schedule of IPV-IPV-bOPV did not sufficiently raise intestinal mucosal immunity against poliovirus type 2, although some cross-immunity was seen. The level of intestinal mucosal immunity was related to shedding status; shedders could produce intestinal mucosa IgA more quickly. The intestinal mucosal immunity level was not related to serum neutralizing antibody level. In the combined sequential vaccination schedule of IPV and bOPV, the risk of circulating vaccine-derived poliovirus type 2 (cVDPV2) may be increased owing to insufficient intestinal mucosal immunity against poliovirus type 2.